Aksesibilitas UI/UX Pada Website Terhadap Penyandang Disabilitas dengan Metode Human Centered Design: Penelitian - Dharma Ajie Nur Rois; Agung Prabowo; Amar Luthfi; Kamal Prohandani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The affordability of information that is easily accessible and accepted by humans in the form of physical, sensory to intellectual is referred to as accessibility. This affordability does not only belong to the disabled, but also to the disabled. However, this accessibility has not fully supported their needs. As on web pages, for example, there are not many websites that pay attention to the affordability of information for people with disabilities. Therefore, we carried out this review to determine the needs of people with disabilities in accessing information, especially on web pages. By using the Human Centered Design or HCD method, we approach users by conducting surveys or questionnaires using the Web Accessibility Content Guidelines (WCAG) to find out the aspects needed on a site. We use the results of the survey as material to measure which needs need to be considered in the Web Accessibility Content Guidelines in designing a web page that is friendly to people with disabilities.